2022
DOI: 10.1097/sap.0000000000003163
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Acellular Dermal Matrix Through Interleukin 4 Enhances Vascular Infiltration

Abstract: BackgroundAcellular dermal matrix (ADM) supported implant-based reconstruction remains the most commonly performed mode of reconstruction after breast cancer. Acellular dermal matrix clinical usage has reported benefits but requires rapid and efficient vascular and cellular incorporation into the recipient to have the best outcomes. Orderly transition from M1 to M2 macrophage phenotypic profile, coordinated in part by interleukin 4 (IL-4), is an important component of vascular stabilization and remodeling. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Prolonging vaccine antigen exposure is another mechanism to increase vaccine efficacy in ECM scaffold materials. ECM contains native protein binding motifs that sequester soluble factors (such as cytokines and growth factors) to extend their half-life and enhance activity, and these properties can be preserved in decellularized tissues [4850]. We found that OVA protein retention was indeed enhanced compared to soluble delivery, possibly via such binding interactions.…”
Section: Discussionmentioning
confidence: 90%
“…Prolonging vaccine antigen exposure is another mechanism to increase vaccine efficacy in ECM scaffold materials. ECM contains native protein binding motifs that sequester soluble factors (such as cytokines and growth factors) to extend their half-life and enhance activity, and these properties can be preserved in decellularized tissues [4850]. We found that OVA protein retention was indeed enhanced compared to soluble delivery, possibly via such binding interactions.…”
Section: Discussionmentioning
confidence: 90%